PENGARUH SOSIALISASI PEMERINTAH, PENGETAHUAN PERPAJAKAN, SANKSI PAJAK, KESADARAN WAJIB PAJAK, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (KECAMATAN BENGKONG) - Helen Stephanie Gusar; Nur Azlina; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Tax has an important role in Indonesia, considering the government’s national development requires relatively large funds. The taxation system in Indoneisa are depending on how Tax payers are being active on fulfilling the obligation of taxation, the requiring a high compliance. This study aims to examine and analyze the effect goverment socialization, tax payer’s knowledge of tax laws, tax penalties, tax payer’s awareness, and service quality of tax authorities against tax compliance in paying taxes on land and buildings (the district Bengkong). The population in this study are all taxpayer land and building located in the subdictrict Bengkong of Batam City. The sampling technique using convenience sampling method and determination of sample size in this study was calculated by using the formula of slovin obtained by 100 respondents. The data of this research is using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The results of this study show that government socialization, service quality of tax authorities have no effect regarding on tax compliance. Viceversa , tax payer’s knowledge of tax laws, tax penalties, tax payer’s awareness have effect on tax compliance.Keywords: socialization, tax laws, tax penalties, service quality, and tax compliance